Modelo de análise da implementação da manufatura aditiva na indústria de implantes ortopédicos - Lima, Anderson Ferreira de (2021)
In the last decade, most orthopedic implants were produced using traditional techniques and in standard sizes and shapes that do not fit perfectly with the patient's bone contour. Additive manufacturing has a significant role in medical applications. Given that the shape of the bone differs from person to person, thanks to the additive manufacturing technology, it is possible to manufacture an implant with a better fit, easy to insert and that reduces the time of surgery. According to Industry 4.0 concepts, smart factories allow the production of items to meet individual customer requirements and even unique items to be manufactured at a profit. In order to fill the gaps necessary to support the medical industry in the adoption of additive manufacturing, the objective of this study is to increase the understanding of how medical companies can implement additive manufacturing for the manufacture of orthopedic implants through the proposal of an analysis model. To this end, a deep vertical scan of the literature was carried out, followed by the identification and analysis of the models and theories already published on additive manufacturing and regulation of medical devices, for the construction of the proposed model and its validation by specialist manufacturers of orthopedic implants. The study shows how the adoption of additive manufacturing for the manufacture of orthopedic implants involves different considerations. In total, 42 criteria were identified that play a relevant role in the implementation decision and for the model to be applicable and to measure the current level of consideration of each criterion, the analysis factor of each criterion and the analysis factor of dimension. For the practical test of the model, the case study method was used in two companies, one that is considering implementing additive manufacturing and another that did not consider it, which demonstrated the sensitivity of the model. The contribution of this study is to present an analysis structure for the implementation of additive manufacturing that encompasses the financial aspects of costs and investments combined with the regulatory aspects for the manufacture of medical devices. Finally, the information presented in this dissertation may assist companies in deciding whether or not to implement additive manufacturing for the manufacture of orthopedic implants, contributing to the management of technology and innovation.